The Effect of Compensation on Employee Job Satisfaction at CV. Bestro Project Sumedang - Firdayanti, Anita; Hidayat, Gustina; Ginanjar, Yayat (SINTESA, 2024)
The problem in this study is that there are still employees on CV. Bestro Project Sumedang who feels dissatisfied at work, one of which is related to compensation. This study aims to determine the effect of compensation on employee job satisfaction in CV. Bestro Project Sumedang. This study uses quantitative research methods with independent variables, namely compensation and dependent variables, namely job satisfaction. The sampling technique is carried out by sampling jenuh technique. The respondents of the study amounted to 30 respondents. Data collection uses observation, interview and questionnaire techniques while data analysis uses validity tests, reliability tests, classical assumption tests, simple linear regression tests, correlation coefficients and determinations and hypothesis tests using partial significance tests (t statistical tests) with data management using SPSS version 29. The results of the research discussing the determination test showed that compensation affected job satisfaction by 26% and the remaining 74% was influenced by other factors that were not discussed the this study. The results of the T test show that compensation has a positive and significant effect on employee job satisfaction in CV. Bestro Project Sumedang